The Effect of Policy Implementation, Budget Allocation, and Leadership on the Capacity of Village Government Apparatuses in Sukabumi Regency, West Java Province - Sapta, Chaerul Dwi; Effendy, Khasan; Lukman, Sampara; Nuryanto, Nuryanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Village government is the spearhead of the administration of government affairs to realize the welfare of the people through the functions of governance, development, development, empowerment of rural communities. The administration of government is determined by the implementation of good government management based on the size of the rights of origin and traditional rights of the village. Thus, the capacity of the apparatus becomes important in administering village government as an independent entity and the lowest level of government following Law Number 6 of 2014. The research method used is a mixture of quantitative and qualitative approaches. The number of samples in this study was 269 respondents, and the research informants were 22 informants. Data analysis used Structural Equation Model and Qualitative Data Analysis. The results of this study indicate that there is a causal relationship between policy implementation. Budget Allocation and Leadership on the Capacity of the Village Government Apparatus, the results obtained are entirely "positive and significant" as indicated by the calculated value (t-value) of each variable greater than 1.96. The distribution of scores across all dimensions is 93% greater in the excellent category. The integration of quantitative methods and qualitative methods obtained the exact most dominant dimensions so that it can be stated that there is a "match." The Daffaryas Digital Apparatus Model is a research finding determined by five factors: bureaucratic structure, attitude disposition, value for money, change-oriented leadership behavior, and task-oriented.In conclusion, the Capacity of the Village Government Apparatus is in a good category. All three hypotheses are accepted. The causality relationship is positive and significant so that new models and concepts of government apparatus capacity are obtained.